Physiological Response of Etawa Goats by Offering Complete Feed Containing Flour of Various Types of Banana Plant Weevil - Bangkit Lutfiaji Syaefullah; Purwanta Purwanta; Aswandi Aswandi (JURNAL TRITON, 2022)
The objective of this research was to observe the Physiological response of Etawa goats which are given complete feed containing flour of various types of banana plant weevil. The study was carried out using a completely randomized design with treatment in the form of 6 complete types of feed with different formulations, consisting of T0, T1, T2, T3, T4, and T5 containing different varieties of banana weevil flour and control treatment (T0). Each treatment in this study was repeated 5 times, so that in total there were 30 experimental units. The media used in this study the form of rumen fluid taken from 30 (thirty) Etawa goats were given a complete feed containing banana weevil flour for 90 days, the Etawa goats used were 30 male. The rumen liquid is sucked using a vacuum pump. Etawa goat mean initial body weight, 18.89 ± 1.87 kg (CV: 12.32%) aged 15-18 months. Livestock are given complete feed containing banana weevil flour for 90 days. Loss-shaped cage measuring 24 mx 6 m as many as 2 units of cages, with a stage-floored construction as high as 140 cm from the ground, inside the cage there is an experimental cage plot measuring 1 x 1 m with a height of 130 cm for Etawa goats. Variables pH, Acetic Acid (mM), Propionic (mM), Butyric Acid (mM) and C2/C3 ratio. Complete feed containing various banana weevil flours had no significant effect on (P> 0.05), while Acid Acetic, Propionic Acid were significantly different (P<0.01).